32.2k views
2 votes
Kayla was asked to rewrite the polynomial expression x2-14x+49

2 Answers

4 votes

Answer:

(x-7)(x-7)

Explanation:

Kayla was asked to rewrite the polynomial expression x2-14x+49-example-1
User Raphie
by
5.8k points
4 votes

Answer:

(x-7)(x-7)

Explanation:

this is a perfect square

x^2-14x+49

take the square of the first number,

X^2 = x times x

the sign of the second number

-14x= (-)

the square of the last number

49= 7x7

to check your work you foil it out

(x-7)(x-7)

x times x = X^2

x times -7= -7x

-7 times x = -7x

-7times -7= 49

then combine like terms

x^2-7x-7x+49 = x^2-14x+49

User James Bond
by
5.9k points